Edukasi Kesehatan Tentang Kebutuhan Minum Air Putih Berdasarkan Berat Badan - Simbolon, Idauli (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Water is the most important need of the human body to function properly and optimally. Consuming enough water can prevent various diseases. However, the problem is that many people ignore drinking water so that their bodies experience dehydration ranging from mild, moderate and severe which causes body functions to not work optimally and even causes various health problems. Among the many factors that cause individuals not to consume enough water, one of them is a lack of knowledge and self-awareness. For this reason, this Community Service activity is to provide health education that aims to increase public knowledge, and increase self-awareness of the importance of drinking water according to the body's needs every day. The method used is the lecture and question and answer method. The results of this PKM found that many participants who attended had limited knowledge about the benefits of water and how much should be consumed each day. This PKM has helped participants in having sufficient knowledge and motivation to consume water regularly and adequately. It is recommended that health education, especially about the importance of drinking water, should continue to be encouraged for all age groups. Of course, all elements of society are invited to participate, especially health workers in this case, especially nurses.